Binge Drinking Prior to Pregnancy Detection in a Nonhuman Primate: Behavioral Evaluation of Offspring. (24th October 2013) - Golub, Mari S.; Hogrefe, Casey E.; VandeVoort, Catherine A.
<x xml:space="preserve">Abstract</x> Background Minimal scientific information is available to inform public health policy on binge drinking prior to pregnancy detection. The nonhuman primate provides a valuable animal model for examining consequences to reproduction and offspring function that may result from this common pattern of alcohol abuse. Methods Adult female rhesus monkeys were dosed with 1.5 g/kg per day ethanol (EtOH) by gavage 2 d/wk beginning 7 months prior to mating and continuing to pregnancy detection at 19 to 20 days gestation. Postnatal evaluation of control (n = 6) and EtOH‐treated (n = 4) infants included a neonatal neurobehavioral assessment, a visual paired comparison (cognitive) test at 35 days of age, and mother–infant interaction at 100 to 112 days of age. Results Alcohol‐exposed neonates did not differ from controls in posture and reflex measures. Longer durations of visual fixation, suggesting slower visual processing, and greater novelty preference were seen in the alcohol group. At early weaning age, as infants spent more time away from their dams, more of the reunions between mother and infant were initiated by the mothers in the alcohol‐exposed group, suggesting a more immature mother–infant interaction. Conclusions Intermittent high‐dose alcohol exposure (binge drinking) discontinued at early pregnancy detection in rhesus monkey can result in altered behavioral function in the infant. Mediating effects on ovum, reproductive tract, and early embryo can be explored in this model. Studies of longer‐term consequences in human populations and animal models are needed.